Analisis Peran Kualitas Produk Dan Penetapan Harga Terhadap Reputasi Merek Produk Kopi Cepat Saji Kopi Kenangan - Sutrisno Sutrisno; Hendy Tannady; Khamaludin Khamaludin; Erna Indriastiningsih; Eka Hendrayani (Management Studies and Entrepreneurship Journal (MSEJ), 2022)
This research aims to show the influence of Price and Product Quality on Kopi Kenangan Brand Reputation. There are three variables in this research including Price, Product Quality and Brand Reputation. The researchist used quantitative methods and the sample used in this research amounted 102 respondents who buyying Kopi Kenangan 3 times or more. The technique used in this research is purposive sampling which is part of non-probability sampling. The research data is analyzed with SPSS 25 shows that Price Variable does not have an influence on Brand Repuation and Quality Product have an influence on Brand Reputation.